Regimes, governos e carga tributária no Brasil (1946-2007) - Schröder, Bruno Henrique Versiani (2009)
This article is concerned in answering if the distinct political regimes in effect in Brazil during the period 1946-2007 have had some impact on the unfolding path of its fiscal burden. Due to the fact that regular elections for the National Congress were hold in the military regime, we also seek to understand in what sense institutions and governmental attributes affect such variable. Therein we have developed a model where the observed results of economic policy emerge from the interaction between institutional incentives and offerers` and demandants` preferences on taxation. Our results suggest that democratic regimes tend ceteris paribus to levy brazilian society less than authoritarian ones and that political instituions are important to understand the process.